Chats and Chunks: Annotation and Analysis of Multiparty Long Casual Conversations - GILMARTIN, EMER; VOGEL, CARL; CAMPBELL, NICK (My University, 2018)
Casual talk or social conversation is a fundamental form of spoken interaction. Corpora of casual talk often comprise relatively short dyadic conversations, although research into such talk has found longer multiparty interaction to be very common. This genre of spoken interaction is attracting more interest with attempts to build more friendly and natural spoken dialog systems. To study longer multiparty casual talk, we have assembled a collection of conversations from three existing corpora. We describe the collection, organization, and annotation of structural chat and chunk phases in these conversations. we then review our preliminary results, noting significant differences in the distribution of overlap, laughter and disfluency in chat and chunk phases, and finding that chunk dominates as conversations get longer. We outline our continuing work on gaining greater understanding of this genre of spoken interaction, with implications for the design of spoken dialog systems.
Eleventh International Conference on Language Resources and Evaluation (LREC 2018)
Keywords: Casual conversation; Multimodal corpus; Annotation; Digital Engagement; Digital Humanities; Telecommunications; Computational linguistics; DIALOG; Discourse & Dialogue; interaction analysis